PENGARUH PEMBELAJARAN DEEP LEARNING DENGAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI MATEMATIKA SISWA SMA - Nur Hasanah, Siti Risna; Anriani, Nurul; Yuhana, Yuyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to examine whether there is a significant difference in the mathematical literacy abilities of students who participate in Deep Learning programs implementing the Problem-Based Learning (PBL) model and those who participate in Deep Learning programs without the implementation of PBL. The study employed a quasi-experimental method using a Nonequivalent Control Group Pretest–Posttest Design. The population consisted of all eleventh-grade students at SMA Negeri 2 Pandeglang in the 2025/2026 academic year. A total of 70 students were selected as the sample through purposive sampling, with 35 students assigned to the experimental group and 35 students to the control group. Data were collected using a mathematical literacy test administered as both a pretest and a posttest. The experimental group received Deep Learning instruction integrated with the Problem-Based Learning model, whereas the control group received Deep Learning instruction without the implementation of Problem-Based Learning. Data analysis was carried out using both descriptive and inferential statistics. The normality test results, based on the Shapiro–Wilk test, indicated that one of the posttest datasets did not meet the assumption of normality. Therefore, hypothesis testing was conducted using the nonparametric Mann–Whitney U test. The findings revealed a significant difference in the mathematical literacy abilities of students who participated in Deep Learning instruction integrated with the Problem-Based Learning model and those who participated in Deep Learning instruction without the implementation of Problem-Based Learning.